Blood copper levels and their influence on reproductive indicators of cows in tropical conditions - Garc?a, Juan Ram?n; Garc?a L?pez, Roberto; Cuesta, M.; Figueredo, J. M.; Qui?ones, R.; Faure, R.; Pedroso, R.; Mollineda, A. (Cuban Journal of Agricultural Science, 2010)
Three hundred and nineteen dairy cows with spontaneous (239) and induced or provoked (80) blood copper deficiency were studied to know the correlation between the blood copper deficiency and the reproductive indicators. The relative risk of the anestrus appearance and the repetition of service in blood copper deficient animals and in those supplemented with copper (Cu) were evaluated. The simple correlation and regression were used to prove the relation of copper with the reproductive indicators. ANOVA was used for comparing the means, and the comparison of the proportions, for estrus and pregnancy. The relative risk was assessed through the software Epidat 3.1 and Win Episcope 2.0. The blood copper deficiency increased 4.93, 2.52, and 3.33 times the risk of having anestrus, repetition of service, and total reproductive problems, respectively. A negative and significant (P < 0.001) correlation was found between the blood copper deficiency and the reproductive indicators in heifers and cows, in a range from 9.8 ? 1.0 to 14.0 ? 0.9 ?mo/L. The doses of 50 and 100 mg of Cu were efficacious to increase the blood copper deficiency and improve the reproductive indicators. Also, they showed protecting effect on the anestrus (P < 0.001) and on the total reproductive problems (P < 0.05). It was concluded that there is negative correlation between the blood copper deficiency and the reproductive indicators, increasing the risk of having anestrus, the repetition of the service, and the main indicators under study. Key words: copper, blood copper deficiency, cows, risk, reproduction.